Phecelurus speciosus (Steud.) Hubb.: A Potential Fodder Grass of Northwest Himalayas - Pant, C.S.; Dhami, K.S. (Asian Journal of Chemistry, 2016)
Phecelurus speciosus (Steud.) Hubb., a perennial indigenous fodder grass of Nainital region (1900–2100 m altitude) of Kumaun Hills was investigated at different stages of development from July to October in 2001–02. This fodder grass was found to contain sufficiently high level of all the chemical ingredients and hence assessed as a good quality fodder.